RUANG LINGKUP STRUKTUR FONOLOGI BAHASA ARAB - Akhmad Najib, Aziz (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2022)
The phonological aspect is considered to have an important role in the beginning of learning Arabic, where in general errors often occur in the phonological aspect of learning Arabic. So this paper will examine the scope of contrastive analysis in the phonological structure of Arabic. This research uses a type of qualitative research with a descriptive approach through analysis and literature study on relevant literature. So the result is that the scope studied from phonology (sound science) includes physiological aspects (articulation) and acoustic aspects (physics). The physiological aspect describes articulation, the position of language sounds and the vibrations of language sounds. As for the acoustic aspect, it discusses issues regarding the influence of the sounds of the language heard which appear in the air in the graphics of the sounds of the language reaching the listener's ear to produce the influence of certain speech sounds. The implications of this research should be that as a teacher or learner of Arabic pay close attention.